Proceedings of the International Conference on Arts and Design Education (ICADE 2018) 2019
DOI: 10.2991/icade-18.2019.62
|View full text |Cite
|
Sign up to set email alerts
|

Student-Centered Approach in Piano Study for Teenagers: Is it possible?

Abstract: Most of music education students who learn piano in Indonesia play the instrument based on teachers' instructions. Teacher-centered approach is commonly found in the learning process in which materials and strategies are determined by the teachers. Fortunately, such learning model is not found in Adorakids Music as one of music learning centers in Bandung. This is due to learning approach by encouraging students' participation in their learning process. Therefore, this study aims to investigate a student-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There are teachers who teach students to use the recorder by applying merely the coordination of recorder fingering of song notes that has led to their students feeling intense pressure and also in the long run, create a sense of frustration and boredom. Tawangsasi, Milyartini, and Virgan (2019) have also found that there were still many teachers who were using a teacher-centred approach while teaching be more meaningful and fun. Music teachers should use every skill and capacity available to them to make music education appealing to students so that the students can benefit in terms of a more meaningful and active learning approach in musical activities.…”
Section: Figure 1 Traditional Music Class Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are teachers who teach students to use the recorder by applying merely the coordination of recorder fingering of song notes that has led to their students feeling intense pressure and also in the long run, create a sense of frustration and boredom. Tawangsasi, Milyartini, and Virgan (2019) have also found that there were still many teachers who were using a teacher-centred approach while teaching be more meaningful and fun. Music teachers should use every skill and capacity available to them to make music education appealing to students so that the students can benefit in terms of a more meaningful and active learning approach in musical activities.…”
Section: Figure 1 Traditional Music Class Configurationmentioning
confidence: 99%
“…There are teachers who teach students to use the recorder by applying merely the coordination of recorder fingering of song notes that has led to their students feeling intense pressure and also in the long run, create a sense of frustration and boredom. Tawangsasi, Milyartini, and Virgan (2019) have also found that there were still many teachers who were using a teacher-centred approach while teaching music. This certainly has gone against the whole idea of a music education, which is to provide the opportunity for students to express feelings, appreciate aesthetics, generate creativity, reduce learning stress and bring positive influences to social progress (Ji, 2016;Swanwick, 2002;Alperson, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…REVISTA DE EDUCAÇÃO E HUMANIDADES, N.º 20, 2022, 137-155. ISSN: 2182 139 además de romper con el esquema de clase centrada en el docente (Tawangsasi et al, 2019), propiciar una mejor asimilación de los contenidos abarcados.…”
Section: Introductionunclassified